Investigating Iraqi EFL Teachers Attitudes Towards the Use of the Internet in Language Teaching: A Case Study at Baghdad and Wassit Universities - Mohsin Gharab, Assist.Prof.Dr. Ali; Mazin Mohammed, Lecturer : (Journal of College of Education, 2021)
The present study aims at investigating Iraqi EFL teachers’ attitude towards the use of the Internet in language teaching .The sample involved includes (40) Iraqi EFL teachers : (25 ) teachers teaching at the Dept. of English , College of Education , University of Baghdad for the academic year (2011-2012) and (15) teachers at the Dept. of English , College of Education for human sciences , Wassit University . For the purpose of data collection , a questionnaire was developed and distributed to the study sample . Surprisingly , it has been found that most of the participants ( 80 % ) had rarely used the Internet for instructional purposes in their classes . Furthermore , results have shown that teachers don’t encourage their students to use the Internet , and (73.4 % ) of them agree that they need special training on how to integrate the Internet in language teaching .